Cities in the Balkans: spaces, faces, memories (Colloquia Comparativa Litterarum, 2025)
Cities in the Balkans: Spaces, Faces, Memories. Roumiana Il. Preshlenova – editor. Sofia, Institute of Balkan Studies & Centre of Thracology, Bulgarian Academy of Sciences, ISBN: 978-619-7179-20-0, https://balkanstudies.bg/images/Cities_in_the_Balkans.pdf. Institute of Balkan Studies & Centre of Thracology.